Equality versus Austerity: Resistance, protests and proposals of the feminist movement - San José, Begoña (Investigaciones Feministas (Feminist Research), 2015)
Neoliberalism, cause of the financial crisis in 2008, governs six years later 80% of the world population by cutting the two major mechanisms of redistribution: worthy jobs and social spending, in a world in which the 8% the population accumulates 82% of the wealth. The relentless rise in inequality attracts influential intellectuals and mobilizes social protest. The "family bed", the familiar strategies of solidarity and the survival against unemployment and cuts, also mutes new cares and new inequalities. The tenacious exit of the women in search of employment until 2013 starts succumbing to the discouragement in 2014, while we are excluded from the tenuous recovery. The feminist movement, revitalized by a wave of young women from the 15M movement, made his major actions against the reform of abortion. By various strategies, the feminist movement incorporates the feminists economics to the social protest. Facing the dismantling of gender equality policies and lack of political discussion of feminist organizations, the NGO Shadow Report to the Committee on the Elimination of All Forms of Discrimination against Women (CEDAW) has opened processes of political incident in 2015; an electoral time in Spain and a time to revive the Schedule Beijing + 20 in the context of objetives of the Sustainable Development.